Waktu Statis: Tawaran Alternatif dalam Memandang Waktu - Lukas Julian (Gerakan Indonesia Kita, 2026)
There are two main theories in contemporary discourse on the concept of time: Dynamic Time Theory and Static Time Theory. In general, humans tend to understand time dynamically due to its intuitive nature. In this paper, I will argue that Static Time Theory is worthy of consideration as a framework for human understanding of the concept of time. Although Dynamic Time Theory has an intuitive affinity with human subjective experiences of time, I will show that its logical construction is weaker than Static Time Theory. Nevertheless, I suggest a hybrid use of the two theories: Dynamic Time Theory in practical contexts, and Static Time Theory in theoretical discussions. Keywords: time, Dynamic Time Theory, Static Time Theory, hybrid.